The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0034-71672010000500016
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias de ensino-aprendizagem na percepção de graduandos de enfermagem

Abstract: The process of teaching consists in determining the entire procedure of education seeking more efficient methods to provide the society of formation. The objective was to evaluate the perception of students of the nursing undergraduate program on the teaching learning strategies experienced. The research is qualitative research which data were collected by a semi-structured interview applied to 12 nursing students. It was made by the content analysis. The data collected led to two categories with their units o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 5 publications
0
13
0
10
Order By: Relevance
“…(12) In this sense, the practice of extensive lectures and without open dialogue with students may reduce the interest in learning and in the performance of students, as well as lead to a lack of link between training and the reality of the profession. (17) The data presented showed that nursing students are vulnerable to stressors that come from living situations and experiencing feelings of responsibility for the life and health of people. Thus, stress can be considered inherent in professional activities of nurses, as well as in academic training in this area.…”
Section: Discussionmentioning
confidence: 94%
“…(12) In this sense, the practice of extensive lectures and without open dialogue with students may reduce the interest in learning and in the performance of students, as well as lead to a lack of link between training and the reality of the profession. (17) The data presented showed that nursing students are vulnerable to stressors that come from living situations and experiencing feelings of responsibility for the life and health of people. Thus, stress can be considered inherent in professional activities of nurses, as well as in academic training in this area.…”
Section: Discussionmentioning
confidence: 94%
“…5 The pedagogic, to assume a significant role, cannot be reduced and/or dedicated only to the teaching of means and mechanisms through which the teaching-learning process were developed, and yes, it shall be a critical way to develop an educational practice that frees from a traditional process, not to be done only by the educator, but by him/her together with the student and the other society members. 19 The care practice experiences by the nursing student in the social and work context, where he/she faces actual and different situations, pushes him/her to perform and mature the professional role with more quality, skill and confidence, when articulating theoretical knowledge with the fact experienced. The praxis is transformative for the student and for the healthcare organization work context, because, when performing an action, the nursing student is based on updated theoretical means that contribute to change and innovate the healthcare services facility.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, for each major intervention performed, use the best way to ascertain and measure the evolution of who is being evaluated to assess its performance and indicate the necessary adjustments. 7 To this end, one realizes the need to build assessment tools that can generate good measurements. Thus, the elaboration of a questionnaire, a test or other Scouting technique requires the observance of care without which it cannot be safely with regard to its results, being fundamental to the quality of fact finding an instrument.…”
Section: -5mentioning
confidence: 99%